Training games : simple and effective techniques to engage and motivate learners - Sugar, Steve; Whitcomb, Jennifer (ASTD Press, 2006)
"One of the most reliable tools to begin building an effective learning environment is through the use of classroom games. This book provides practical, step-by-step advice on how to select just the right game for an event, choose the format, facilitate the event, and evaluate your effectiveness. The authors provide 11 classroom-tested games that are easily adapted to liven up any learning event. The CD-ROM contains templates and worksheets you can start using immediately."--Jacket